Biomechanical Comparison of FiberTape Device Repair Techniques of Ligamentous Lisfranc Injury in Cadaveric Model. Issue 4 (22nd October 2020) - Koroneos, Zachary; Vannatta, Emily; Kim, Morgan S.; Fritsche, Madelaine W.; Cowman, Trevin; Kunselman, Allen; Lewis, Gregory; Aynardi, Michael C.
Category: Trauma; Basic Sciences/Biologics; Midfoot/Forefoot; Sports Introduction/Purpose: Lisfranc ligamentous injuries are complex. Controversy exists regarding their treatment and preferred method of fixation. Fixation methods employing a FiberTape device and interference screw fixation have been described as an alternative to traditional screw fixation. The purpose of this biomechanical study was to evaluate two methods of fixation utilizing interference screw fixation with FiberTape augmentation in a cadaveric model. Methods: 9 paired cadaveric feet (mid tibia/fibula) were separated into two groups based on fixation method: FiberTape alone and FiberTape with supplementary limb into the middle cuneiform via anchor. At three joints of the midfoot (second metatarsal - medial cuneiform, intermediate cuneiform - medial cuneiform, second metatarsal - intermediate cuneiform), the diastasis and relative angular displacement between bones in the coronal plane were measured for static and cyclic loading. Measurements were obtained for the native (pre-injured), injured, and post-fixation in static loading. Fixed specimens then underwent stepwise increases in cyclic loading performed at 1 Hz and 100 cycles, at 100 N intervals from 500 to 1800 N ground reaction force. The Achilles tendon was also loaded to simulate postoperative weightbearing. Failure of fixation was defined as diastasis at the second metatarsal - medial cuneiform joint greater than 2 millimeters. Results: FiberTape specimens demonstrated diastasis failures of 3 of 9 (33%) specimens at cyclic loads of 1000 N. Conversely, FiberTape with supplementary limb specimens all survived past this loading magnitude, with 1 failing at supraphysiologic loads (>1200 N). The difference in diastasis at the second metatarsal-medial cuneiform joint was statistically significant between the two groups at forces of 1600N (p = 0.019) and 1800N (p = 0.029). There were no significant differences between the other joint diastases and relative angular displacements. Conclusion: The use of FiberTape for fixation of ligamentous Lisfranc injuries appears to provide a biomechanically viable alternative for withstanding early post-operative protected weightbearing. Furthermore, the use of a supplementary limb in addition to the FiberTape fixation method appears to enhance its biomechanical efficacy under cyclic loading especially at higher loads.